A parents guide to television, Making the Most of It - Kelley, Michael R. (New York John Wiley and Sons Inc, 1983)
Discusses the impact of television on a child and suggests methods for using television viewing to improve childrens communication skills, imagination, and critical thinking
Keywords: Art